Representasi Budaya Bali dalam Film Komang (Analisis Semiotika Roland Barthes) - Gayatri Dewi; Flora Meliana Siahaan; George Wilhelm Bender (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study analyzes the representation of Balinese culture in the film